Bell, book & candlemas - Hesse, Jennifer David (Hesse, Jennifer David. Wiccan wheel mystery., 2017)
The Wiccan holiday of Candlemas is right around the corner, but when vandals target New Age gift shop Moonstone Treasures, the mood is far from festive. Frightening threats and accusations of witchcraft aimed at the owner have some Wiccan patrons calling it a hate crime. And when things escalate to murder, the community turns to Keli. As a friend and customer, Keli wants to help. But there's one problem: she's fiercely private about her religion. How can she stop the harassment, not to mention catch a killer, while keeping her faith hidden from her colleagues, clients, and her promising and long awaited new boyfriend? At a time meant to banish darkness, will Keli have to choose between risking the spotlight and keeping her beliefs locked in the proverbial broom closet? Or will she call on her deepest convictions to conjure the perfect path?